Oxidation Behavior at 1600 °C of Si‐SiC‐ZrB2 Composites Produced by Si Reactive Infiltration1. Issue 2 (4th October 2013) - D'Amico, Giuseppe Claudio; Ortona, Alberto; Biamino, Sara; Fino, Paolo; Badini, Claudio; D'Angelo, Claudio
<x xml:space="preserve">Abstract</x> Si–SiC–ZrB2 are produced by the reactive infiltration with molten silicon in porous SiC–C–ZrB2 preforms. It is observed that oxidized Si–SiC–ZrB2 ceramics present a layered structure composed of an outer layer of silica and a borosilicate glass intermediate layer with ZrO2 particles and the unoxidized bulk material. The graphs show that the passivation is very effective already after 5 min of oxidation. The thermograms do not vary significantly when the oxidation times are increased. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>